Experimental particle production in time-dependent spacetimes: a one-dimensional scattering problem - Sparn, Marius; Kath, Elinor; Liebster, Nikolas; Duchene, Jelte; Schmidt, Christian F.; Tolosa-Simeón, Mireia; Parra-López, Álvaro; Floerchinger, Stefan; Strobel, Helmut; Oberthaler, Markus K. (Physical review letters, 2024)
We experimentally study cosmological particle production in a two-dimensional Bose-Einstein condensate, whose density excitations map to an analog cosmology. The expansion of spacetime is realized with tunable interactions. The particle spectrum can be understood through an analogy to quantum mechanical scattering, in which the dynamics of the spacetime metric determine the shape of the scattering potential. Hallmark scattering phenomena such as resonant forward scattering and Bragg reflection are connected to their cosmological counterparts, namely linearly expanding space and bouncing universes. We compare our findings to a theoretical description that extends beyond the acoustic approximation, which enables us to apply the model to high-momentum excitations.
Gesehen am 21.08.2025